The creative university : contemporary responses to the changing role of the university - Lund, Birthe; Arndt, Sonja (Creative education (Sense Publishers), 2018)
The concept behind the Creative University is about knowledge cultures, critical creative thinking and innovative learning processes, situating the university as flexible, open and responsive to contemporary educational ideologies. Its vision reflects world-wide interest in students' engagement with diverse knowledges that challenge and break with habitual actions and thought and elevates creativity as central to the design of new and innovative pedagogies. In The Creative University: Contemporary Responses to the Changing Role of the University, leading authors position the university to inviting exploratory constructions and approaches that respond to past, present and future social and educational tensions and developments. This volume is a provocation for discovery, fostering and critiquing creativity, and advancing innovation.